2015
DOI: 10.1530/erp-14-0003
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular ejection fraction assessment by non-cardiologists from transverse views using a simplified wall motion score index

Abstract: For the non-cardiologist emergency physician and intensivist, performing an accurate estimation of left ventricular ejection fraction (LVEF) is essential for the management of critically ill patients, such as patients presenting with shock, severe respiratory distress or chest pain. Our objective was to develop a semi-quantitative method to improve visual LVEF evaluation. A group of 12 sets of transthoracic echocardiograms with LVEF in the range of 18–64% were interpreted by 17 experienced observers (PRO) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42]. All studies showed feasibility to train medical students to perform ultrasonography after a relatively short amount of training, which is comparable to the training medical students received in our study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39]. Four other studies used a point-of-care ultrasonography training program to determine diagnostic performance in various clinical scenarios [36,[40][41][42]. All studies showed feasibility to train medical students to perform ultrasonography after a relatively short amount of training, which is comparable to the training medical students received in our study.…”
Section: Discussionsupporting
confidence: 74%
“…The studies reporting on image quality showed percentages of (at least) adequate imaging ranging from 89 to 98%, unfortunately by non-independent judging [3,7]. Furthermore, after training, medical students can adequately interpret images with a very simplified or binary assessment [36]. A number of previous studies employed training curricula for medical students on ultrasonography protocols [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a semi-quantitative method dedicated specifically to emergency and critical care physicians based on the simple assessment of normokinesia (EF = 60%), hypokinesia (EF = 40%) or akinesia (EF = 20%) in the 3 short-axis views was superior to global visual estimation ( 20 , 21 ). In the current study, we applied the new segmental EF 15-40-65 score in TTE to each of the 16 segments of the polar map and obtained a global LVEF resulting from the arithmetic mean of all segmental EF.…”
Section: Discussionmentioning
confidence: 99%
“…13 As emergency physicians become more experienced with cardiac POCUS, more advanced applications are being investigated such as valvular assessment, regional wall motion, and diastolic function. [14][15][16] As a consequence of this increased experience with cardiac POCUS, emergency physicians may be able to identify if the heart does not appear normal because of other important cardiac abnormalities. In this case, the emergency physician identified a structural cardiac abnormality using POCUS that led to the request for an expedited inpatient workup.…”
Section: Discussionmentioning
confidence: 99%